QUALITY OF LIFE AMONG ELDERLY OSTOMATES: A LITERATURE REVIEW - Le, Daniel (Acta Scientiae et Intellectus, 2024)
Ostomy formation can have profound impact on the individuals undergoing such procedures. Multiple aspects of an individual’s life are affected. Quality of life (QOL) is a measure of daily life satisfaction and is affected by physical, emotional, and psychological factors (Slater, 2010). To further understand the effects of ostomy formation and QOL, much research and scholarly publications have been undertaken. While there is a notable amount of available literature regarding ostomies and QOL, there is a scarce amount that specifically speaks to QOL and ostomy formation among the elderly population. This is surprising given the prevalence of ostomy formations in older individuals. Additionally, this topic carries important relevance given the growing rate of today’s elderly population. As such, a literature review is provided with an aim to address an evident gap in literature regarding the specific impact of ostomies on QOL among the elderly. Areas of focus pertaining to QOL are organized in three major themes and include physical, emotional, and psychological factors. Subtopics relevant to each theme are provided. Conflicting research is included as well. Overall, there is a clear lack of literature that addresses specific ostomy-related challenges faced by the elderly. Even more lacking is the amount of literature that makes the connection of ostomy-related challenges to QOL among this population. More research is warranted given the lack of available of literature, growing elderly population, and the need to better understand and care for this unique population.